Oral Health-Related Quality of Life, Dry Mouth Sensation, and Level of Anxiety in Elderly Patients Rehabilitated with New Removable Dentures - Bannwart, Lisiane Cristina [UNESP]; De Moraes Melo Neto, Clóvis Lamartine [UNESP]; Goiato, Marcelo Coelho [UNESP]; Dos Santos, Daniela Micheline [UNESP]; Da Silva Paiva, Cristina Aparecida; De Araújo Moreno, Nathaly Vilene; Da Silva, Emily Vivianne Freitas [UNESP]; De Magalhães Bertoz, André Pinheiro [UNESP] (Thieme, 2021)
Objective  This study aimed to evaluate the influence of new complete dentures (CDs) and new removable partial dentures (RPDs) on oral health-related quality of life, dry mouth sensation, and anxiety level of their wearers. Materials and Methods  In total, 20 complete edentulous patients (in both arches) that needed to be rehabilitated with new CDs, and 20 partial edentulous patients (in both arches) that needed to be rehabilitated with new RPDs, were included in this study. Each patient must wear the same pair of CDs or RPDs for more than 5 years. Oral health-related quality of life, dry mouth sensation, and level of anxiety were assessed by using the following questionnaires: Geriatric Oral Health Assessment Index (GOHAI), VAS (Visual Analog Scale) Xerostomia Questionnaire, and State-Trait Anxiety Inventory (STAI). These questionnaires were applied before oral rehabilitation (initially initial time point) and 3 months after insertion of new dentures (end time point). Statistical Analysis  For the results of STAI-State, STAI-Trait, and GOHAI, the Wilcoxon test was applied to compare the time points. For the results of the VAS xerostomia questionnaire, two-way repeated measures ANOVA (analysis of variance) was applied, followed by the Tukey test. The p -values lower than 0.05 were considered statistically significant. Results / Conclusion  For both groups, it was observed that 3 months after the insertion of new removable dentures: (1) there was an increase in oral health-related quality of life; (2) there was a reduction in anxiety (trait anxiety and state anxiety); and (3) there was a perception of greater salivation.
Keywords: anxiety; complete denture; Geriatric Oral Health Assessment Index; quality of life; questionnaires; removable partial denture; satisfaction; State-Trait Anxiety Inventory; Visual Analog Scale; xerostomia